Literature in the modern world : critical essays and documents (Oxford University Press, 2004)
"Literature in the Modern World offers a unique combination of English, European, American, and post-colonial perspectives on literary study from the 1920s to the present day. Carefully introduced and arranged to highlight the development of debates, it is designed to engage newcomers to the field with some of the main themes and issues that will concern them as readers of modern literary texts of all genres." "This fully revised and updated second edition now also includes important pieces by, amongst others, T.S. Eliot, Michel Foucault, and Salman Rushdie, and has been extended to include more writers and critics from the world beyond Europe. In addition, there is an increased focus on questions of gender and identity, and two wholly new sections, on 'literature and nation' and 'literature and value'."--Jacket.